Expression profiles of genes involved in TLRs and NLRs signaling pathways of water buffaloes infected with Fasciola gigantica - Zhang, Fu-Kai; Hou, Jun-Ling; Guo, Ai-Jiang; Tian, Ai-Ling; Shi, Wei; Sheng, Zhao-An; Zheng, Wen-Bin; Huang, Wei-Yi; Elsheikha, Hany M.; Zhu, Xing-Quan (Elsevier, 2018)
Infection of ruminants and humans with Fasciola gigantica is attracting increasing attention due to its economic impact and public health significance. However, little is known of innate immune responses during F. gigantica infection. Here, we investigated the expression profiles of genes involved in Toll-like receptors (TLRs) and NOD-like receptors (NLRs) signaling pathways in buffaloes infected with 500 F. gigantica metacercariae. Serum, liver and peripheral blood mononuclear cell (PBMC) samples were collected from infected and control buffaloes at 3, 10, 28, and 70 days post infection (dpi). Then, the levels of 12 cytokines in serum samples were evaluated by ELISA. Also, the levels of expression of 42 genes, related to TLRs and NLRs signaling, in liver and PBMCs were determined using custom RT2 Profiler PCR Arrays. At 3 dpi, modest activation of TLR4 and TLR8 and the adaptor protein (TICAM1) was detected. At 10 dpi, NF-κB1 and Interferon Regulatory Factor signaling pathways were upregulated along with activation of TLR1, TLR2, TLR6, TLR10, TRAF6, IRF3, TBK1, CASP1, CD80, and IFNA1 in the liver, and inflammatory response with activated TLR4, TLR9, TICAM1, NF- κB1, NLRP3, CD86, IL-1B, IL-6, and IL-8 in PBMCs. At 28 dpi, there was increase in the levels of cytokines along with induction of NLRP1 and NLRP3 inflammasomes-dependent immune responses in the liver and PBMCs. At 70 dpi, F. gigantica activated TLRs and NLRs, and their downstream interacting molecules. The activation of TLR7/9 signaling (perhaps due to increased B-cell maturation and activation) and upregulation of NLRP3 gene were also detected. These findings indicate that F. gigantica alters the expression of TLRs and NLRs genes to evade host immune defenses. Elucidation of the roles of the downstream effectors interacting with these genes may aid in the development of new interventions to control disease caused by F. gigantica infection.